A Retrospective Study Concerning Drug Utilization Evaluation in COVID- 19 Patients - Ramanath , K. V.; Venugopal, Sharvari; Shadakshari, A.; Pradhan, Nimesh Kumar; Abinavi, B.; Kaur, Harsharan; Jacob, Leeba (Research Developments in Medicine and Medical Science Vol. 1, 2023)
Corona disease 2019 (COVID-19) is an airborne viral infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mutants. Transmission can occur if contaminated fluids are splashed or sprayed into the eyes, nose, or mouth, or, in rare cases, through contaminated surfaces. The standard diagnostic method and treatment pattern varies from hospital to hospital, which provokes carrying out this work. The study aims to assess the drug treatment pattern, antibiotic usages patterns, and cost and determine the antiviral usage pattern and price. This retrospective observational study was conducted in Sagar Hospitals, Kumaraswamy Layout, Bangalore, for six months after obtaining ethical clearance using a well-designed questionnaire. The medical records department provided 155 cases. The findings showed that Ceftriaxone, a cell wall synthesis inhibitor, was the most commonly used antibiotic (60.6%), followed by Azithromycin, a protein synthesis inhibitor (59.4%). Oseltamivir was the most commonly used antiviral in 51.6% of patients, Remdesivir in 41.3%, and Favipiravir in 12.3%. Other co-morbid drugs are corticosteroids, immunomodulators, mucolytics, antihistamines, blood thinners, and anti-helminthes. The mean cost of the antibiotics and antiviral are 224 ± 295.73; 1623.28 ± 2047.45. This study demonstrated that the ICMR Guidelines were followed in the management of COVID-19. The cost of the medications, particularly antibiotics, antivirals, and immunomodulators, had a big impact on the treatment regimens chosen. Therefore, cost consideration studies may aid in promoting rational medicine use and reducing costs associated with disease management.